In-vitro effect of the methanolic extract of Momordica charantia on hatching of eggs of Haemonchus sp. - Jaramillo Hernández, Dumar Alexander; VÁSQUEZ TRUJILLO, Adolfo; LESMES RODRÍGUEZ, Lida Carolina (Vitae, 2021)
Background: Endoparasitism, particularly infections by gastrointestinal nematodes (e.g., Haemochus sp.), has been associated with economic losses within sheep production systems in tropical regions. Thus, implementing therapeutic alternatives that are environmentally sustainable is essential for parasite integral control programs. Objectives: Evaluate in-vitro the effect of Momordica charantia methanolic extract on the Haemonchus sp. eggs' hatching process. Methods: Nematode eggs were retrieved from experimentally infected sheep and exposed to 10, 20, 40, 80, and 160 mg/mL of methanolic extract of M. charantia. Hatching percentages were recorded from five replicates, and CL50 and CL90 were estimated through Probit regression analysis. Results: A significant effect on the hatching percentages were observed, from 24.2% up to 84.6% inhibition (p<0.05). The LC50 and LC90 estimated were 52.2 mg/mL (95%CI 37.87-63.22) and 201.45 mg/mL (95%CI 186.01-221.89), respectively. Utilizing a preliminary phytochemical analysis, potential antihelmintic compounds such as alkaloid, triterpenes, and anthracenic glycosides groups were identified in the methanolic extract. Conclusions: In the in-vitro test, the methanolic extract of M. charantia was effective in inhibiting the hatching of Haemonchus sp., which is important to promote other bio-guided fractionation studies of this plant on different life stages of H. contortus, this being a plant species widely adapted to the conditions of the piedmont (foothills) of Meta, Colombia.